1987
DOI: 10.1111/j.1440-1819.1987.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

The Application of DSM‐III Diagnostic Criteria to School Refusal

Abstract: The DSM‐III diagnostic criteria were applied to school refusal cases, and the possibility of a subclassification of school refusal through the DSM‐III was studied. The subjects were 50 cases diagnosed as school refusal following the criteria defined by Sumi and Tatara. As for the Axis I diagnoses, the subjects fell under the separation anxiety disorder (7 cases), avoidance disorder (13 cases), overanxious disorder (8 cases), identity disorder (5 cases), adjustment disorder (11 cases) and others. On Axis II, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…This is similar to other clinic-based studies on school refusal where more severe forms have been reported. 7,8 Temperamental difficulties were found in a high proportion of the subjects (69.7%) as reported in earlier studies. 4 Depressive disorders were the commonest diagnoses in the present study (63.6%), which is similar to recent literature on school refusal.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is similar to other clinic-based studies on school refusal where more severe forms have been reported. 7,8 Temperamental difficulties were found in a high proportion of the subjects (69.7%) as reported in earlier studies. 4 Depressive disorders were the commonest diagnoses in the present study (63.6%), which is similar to recent literature on school refusal.…”
Section: Discussionsupporting
confidence: 83%
“…Appropriate treatment of depression using antidepressants and psychosocial interventions may help speedy return to school. High rates of anxiety disorders 7,6 have been reported in younger children. Nineteen (57.6%) subjects had anxiety disorders in our study, which included separation anxiety disorder, specific phobias, obsessive compulsive disorder and generalized anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Reports of the prevalence of depressive symptoms and depressive disorders in children exhibiting school refusal vary considerably. [4,26,27] More pervasive and persistent oppositional behaviour, as encompassed in oppositional defiant disorder, has been reported in between 9 and 21% of anxious children exhibiting school refusal. [11,14] As many as 50% of children may display subclinical depression (i.e.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In another study, Buitelaar et al investigated the DSM‐III diagnoses at first visit of 25 school refusers, and report diagnoses of anxiety disorder in eight (32%), depressive disorder in seven (28%), somatoform disorder in six (24%), and conduct/personality disorder in four (16%) cases 16 . In addition, Hoshino et al conducted a similar study on DSM‐III diagnoses in 50 cases of school refusal in Japan, and reported the principal diagnosis as being separation anxiety disorder in seven (14%), avoidance disorder in 13 (26%), over‐anxious disorder in eight (16%), identity disorder in five (10%), and adjustment disorder in 11 (22%) cases, among others, while also commenting on difficulties in applying DSM‐III diagnosis to school refusal 17 …”
Section: Discussionmentioning
confidence: 99%